2021
DOI: 10.3389/fpsyg.2021.732865
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Analysis of the Influence of Timbre on Affect Perception in Western Classical Music and Chinese Music Traditions

Abstract: Timbre is one of the psychophysical cues that has a great impact on affect perception, although, it has not been the subject of much cross-cultural research. Our aim is to investigate the influence of timbre on the perception of affect conveyed by Western and Chinese classical music using a cross-cultural approach. Four listener groups (Western musicians, Western nonmusicians, Chinese musicians, and Chinese nonmusicians; 40 per group) were presented with 48 musical excerpts, which included two musical excerpts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
1
6
1
Order By: Relevance
“…However, the present study shows that the “anger” excerpt conveyed neutral and highly arousing emotion. Wang et al ( 2021 ) reported a consistent result in which “anger” in Chinese traditional music is a neutral and highly arousing emotion. Such a result indicates that Chinese traditional music has distinct emotional characteristics in the angry dimension.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the present study shows that the “anger” excerpt conveyed neutral and highly arousing emotion. Wang et al ( 2021 ) reported a consistent result in which “anger” in Chinese traditional music is a neutral and highly arousing emotion. Such a result indicates that Chinese traditional music has distinct emotional characteristics in the angry dimension.…”
Section: Discussionmentioning
confidence: 90%
“…In previous studies using Western music, neutral, tenderness, and peacefulness music were found to represent neither positive nor negative valence type (Paquette et al, 2013 ; Prada et al, 2018 ; Eerola & Vuoskoski, 2011 ; Fuentes-Sánchez et al, 2021 ; Wang et al, 2021 ). Consistently, in the present study, while the “gentleness” and “solemnness” excerpts were moderately arousing and the “peacefulness” and “transcendence” ones less arousing, they all demonstrated neutral valence.…”
Section: Discussionmentioning
confidence: 93%
“…Classified by region and country, music from different regions reflects their respective cultural characteristics and traditions. For example, Chinese music is famous for its unique pentatonic scale, strong expressiveness, and rich variety of instruments ( Wang et al, 2021 ; Su and Kong, 2023 ). The characteristics of Indian music are complex rhythmic structures, such as Tala, and improvisation based on the scale (Raga; Fletcher, 1915 ; Sharma et al, 2021 ).…”
Section: Definition and Classification Of Musicmentioning
confidence: 99%
“…Stereotypes of a culture may also have an impact on one’s perception of music from specific cultures [ 44 ]. Wang et al [ 45 ] compared the impact of musical background and cultural background on the perception of emotions by Chinese and Western participants. They found cultural background to have a larger impact as compared to the musical background of a participant.…”
Section: Related Workmentioning
confidence: 99%